The Impact of Continuous Training on Maximizing Efficiency in Tax Administration: The Case of a State Internal Revenue Service (SIRS) in the North Central Region of Nigeria - Muritala Awodun, PhD; Faizu Edu, PhD (International Journal of Applied Business and International Management, 2018)
The purpose of this study is to establish the role of continuous training in maximizing efficiency in tax administration using the case of a State Internal Revenue Service (SIRS) in the North Central Region of Nigeria. The study examined the strategies adopted for continuous training by the SIRS and subsequently measured the impact of these strategies on the performance of all levels of management (low, middle and top) of the SIRS under focus. The SIRS identified the need for training from its inception and built into its process the entry training programme (of 3 months) for all staff, the monthly field feedback and training (of a day monthly) for all staff, directorates’ regular technical training, professional trainings, and leadership and management trainings (both local and international). These schedule five stage trainings have become a closely knitted continuous training strategy that has improved the skills and capacities of the employees of the SIRS. To ascertain the extent to which the above have impacted on the employees, the SWOT Analysis was adopted along with the appraisal of five set of questionnaires applied to 642 staff of the SIRS present at a particular month field feedback session. The five set of questionnaires were designed to measure; (1) the state of change readiness of employees of the SIRS for service excellence, (2) the state of change thinking of employees of the SIRS for service excellence, (3) the state of resistance to change by the employees of the SIRS, (4) the state of resistance to going through the process of change by the employees of the SIRS, and (5) the state of resistance to leaving the current state for the desired state of excellence. All these are targeted towards measuring the state of readiness for change, through continuous training, on the employees’ commitment, efficiency and performance. The above is in addition to the analysis of the individual strengths and weaknesses that culminates in the organizational strengths and weaknesses, including the environmental opportunities and threats which have a significant role to play on the organizational performance. The findings revealed that between 73 - 87 percent of the staff of the SIRS are change ready, with positive change thinking mentality, not resistant to change, not resistant to going through the change process, and are not resistant to leaving the current state for the desired state of excellence. Ultimately, the study concludes that there is a positive relationship between continuous training, and employee commitment and job satisfaction, on the one hand, and continuous training and performance excellence as relating to efficiency and effectiveness in tax administration, on the other hand. This study is a pioneer one that extends the employee commitment debate to the Internal Revenue Service, using this SIRS as a case study. It provides an explanation, with empirical evidence, by demonstrating that training extends direct positive effect on employee commitment in revenue administration. The study also demonstrates that, in the revenue administration, job satisfaction helps to transmit the effect of continuous training on employee commitment and performance excellence.